2020
DOI: 10.1074/mcp.ra120.001938
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Profiling Reveals Protein Oscillation, Phosphorylation, and Localization Dynamics

Abstract: The cell cycle is a highly conserved process involving the coordinated separation of a single cell into two daughter cells. To relate transcriptional regulation across the cell cycle with oscillatory changes in protein abundance and activity, we carried out a proteome- and phospho-proteome-wide mass spectrometry profiling. We compared protein dynamics with gene transcription, revealing many transcriptionally regulated G2 mRNAs that only produce a protein shift after mitosis. Integration of CRISPR/Cas9 survivab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 47 publications
6
36
0
Order By: Relevance
“…The frequency of PsPs identified (1.7%, 119 / 6,899) compares well with a recent antibody-based screen for cell cycle regulated proteins (2.6%, 331 / 12,390) [48]. Included in 331 hits are proteins that vary in subcellular localization but not abundance across the cell cycle, consistent with other datasets using biochemical fractionation [49]. PsPs identified in this study will be limited to proteins that change in abundance.…”
Section: Discussionsupporting
confidence: 80%
“…The frequency of PsPs identified (1.7%, 119 / 6,899) compares well with a recent antibody-based screen for cell cycle regulated proteins (2.6%, 331 / 12,390) [48]. Included in 331 hits are proteins that vary in subcellular localization but not abundance across the cell cycle, consistent with other datasets using biochemical fractionation [49]. PsPs identified in this study will be limited to proteins that change in abundance.…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, mutations in TP53 were associated with an increase in phosphorylation of proteins involved in DNA damage repair pathways (e.g., MSH6, TP53, and TP53BP1), which suggests that these alterations play a role in maintaining genome integrity and preventing apoptosis (Figure 2C). In TP53 mutant tumors, we also observed higher phosphorylation of MKI67, a marker for cellular proliferation, which implies that these mutations may lead to increased cell growth rates (Herr et al, 2020). We further explored the effects of TP53 missense mutations compared to truncating mutations and observed a significantly greater cis-effect with higher TP53 protein expression and TP53-S315 phosphosite expression in the TP53 missense group compared to the wild-type group (Figure S2A), while there were no significant TP53 protein changes in cis-effects between the truncation and wild-type groups (Figure S2A).…”
Section: Proteogenomic Landscape Of the Pdac Cohortmentioning
confidence: 60%
“…maintenance during DNA replication [31]. This study pointed out a significant role of MAT2A in cell cycle and possibly cell proliferation.…”
Section: Resultsmentioning
confidence: 51%
“…Proteome-wide mass spectrometry profiling revealed that MAT2A is among the cell cycle-dependent translocating proteins. Further analyses indicated that MAT2A may translocate to the nucleus after the G1/S-checkpoint, which enables epigenetic histone methylation maintenance during DNA replication [31]. This study pointed out a significant role of MAT2A in cell cycle and possibly cell proliferation.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation